Comparação de métodos de dimensionamento em redes de distribuição de água - Maia Júnior, José Valmir Farias (2012)
This work presents a computational model for the dimensioning of optimized minimum cost of water distribution network. The model is an addition to the system UFC4(module for dimensioning water supply networks). The model uses the technique of Genetic Algorithms and the hydraulic simulation is done by EPANET. Multiple simulations have been made individually varying each parameter in the algorithm to achieve better performance in terms of convergence, processing time and the final of the quality solutions. Its results is compared to that obtained by LENHSNET for the same network. The cost compared was the of implementation of pipes. The proposed model has proved satisfactory for optimized dimensioning of network.